Laksamana Cheng Ho Muslim Cina dan Tokoh Mitologi - Muhammad Ikhsan Tanggok (Buletin Al-Turas, 2005)
Cheng Ho (Sam Poo Kong) is a sailor (seaman) and Chinese Moslem merchant. In the 14th century he arrived at Semarang, Central Java, Indonesia. In respect to his visit, the people built a temple called Sam Poo Kong. He was supposed to be a god because of his blessing for the people who worshiped in that temple. In this ritual, activity appeared a concept of exchangeresulted from Javanese and Chinese cosmology